The Effect of Compensation and Work Discipline on Employee Performance with Work Motivation as an Intervening Variable - Kholik, Jajang Roni Aunul; Madiistriyatno, Harries; Taufik, Kemal (East Asian Journal of Multidisciplinary Research, 2024)
Human resources (HR) play a key role in the success and sustainability of a company because employee capability and performance are very vital elements. Two main factors that are often associated with employee performance are compensation and work discipline. This study aims to determine and analyze the direct and indirect effects of compensation and work discipline on employee performance with work motivation as an intervening variable at PT. Bukit Alam Persada. The research method was carried out using a quantitative approach to PLS-SEM analysis using SmartPLS 4 software with a sample of 35 employee staff obtained by using a questionnaire. The study's findings demonstrated that while compensation has a positive and significant impact on work motivation, work discipline has a negative and negligible impact on work motivation; compensation has a positive and significant impact on employee performance; work discipline has a positive and significant impact on employee performance; work motivation has a positive and significant impact on employee performance; compensation has a positive and significant impact on employee performance through work motivation; and work discipline has a negative and negligible impact on employee performance through work motivation.